Meningkatkan Keaktifan Siswa Melalui Penerapan Problem Based Learning di Sekolah Minggu Buddha (SMB) Saraniyadhamma Vihara Giri Metta Bhavana Arama Lombok Utara - Susilawati, Ela; latifah; Lestari, Puji (Jounal Nyanadassana, 2025)
This research aims to increase student activity by using the Problem Baset Learning learning method at the Saraniyadhamma Vihara Giri Metta Bhavana Arama Buddhist Sunday School, North Lombok. This type of research uses Class Action Research (PTK). The research subjects were 10 Buddhist Sunday School (SMB) students at Majjhima Sekkha (junior high school) and Maha Sekkha (high school/vocational school equivalent). Data collection techniques are observation, interviews, questionnaires and documentation. Data analysisi is the form of PTK or observation to determine the level of activity of SMB students through the Problem Baset Learning learning method by looking at indicators of student activity. The results of the research show that student activity through the problem base learning method can be proven by pre-action results that none of the 10 students have reached the level of student activity, the average student scored very less active. Cycle I experienced an increase with 2 students who were very active (9-10). In cycle II there was an increase again to 10 students reaching a level of student activity with a score of 9-10 (very active). This can be seen from the results of observations with indicators of frequency of asking, response to teacher questions, and initiative in completing assignments. It can be concluded that the application of the problem ased learning method is said to be effective in increasing the activity of Saraniyadhamma Vihara Giri Metta Bhavana Arama Buddhist Sunday School students.